Focal 123I-MIBG Uptake in the Medial Segment of the Normal Liver. (March 2019) - Matsusaka, Yohji; Nakahara, Tadaki; Iwabuchi, Yu; Minami, Yasuhiro; Jinzaki, Masahiro
Abstract : Abstract: An 84-year-old man with parkinsonism was referred for 123 I-MIBG scintigraphy. Abnormal uptake in the right upper abdomen was incidentally seen in planar image, and SPECT revealed focal uptake in the medial segment (S4) of the liver. Subsequent triple-phase contrast-enhanced CT showed no evidence of hepatic tumors, although in the arterial phase, there were an enhanced region corresponding to the uptake area and the enhanced vein of Sappey that flowed into S4. In this case, the focal 123 I-MIBG uptake would be attributable to hemodynamic change in the liver.